Threats of fall armyworm (Spodoptera frugiperda) incidence in Nepal and it’s integrated management-A review - Bhusal, Sudhan; Chapagain, Enjila (Journal of Agriculture and Natural Resources, 2020)
Fall Armyworm (Spodoptera frugiperda) is in the state of major threat for Nepal especially in maize although it has more than 80 host to continue its life cycle. After its first incidence in Africa in 2016, it has already spread in more than 100 countries within a short period of time. It was seen in India for the first time in 2018. Due to the open border between Nepal and India, there is high probability of incidence of pest in Nepal. The temperature regime of Nepal is highly suitable for the pest establishment. Now is the time to think about the pest which can cause severe damage to the second most produced cereal crop of Nepal i.e. maize. Management of the pest is possible through many biological, chemical and cultural means. Planting of legumes as a trap crop and ploughing field properly before planting the field can be a best possible cultural method of managing the pest. Natural enemies like Telenomus, Trichogramma chilotraeae for controlling the eggs, Bacillus thuringiensis for larvae and Brachymeria ovata for pupa of Fall Armyworm in Maize and Vegetables. Similarly, Neem extracts are found be larvicidal and the oil extracted from the seeds of long pepper are found to be checking Spermatogenesis of the pest. Chemicals like Methomyl, Cyfluthrin, Methyl parathion are used tocontrol the pest. Use of chemicals at the initiation of the pest spread is discouraged as it can hamper the natural enemy present in the surrounding ecology. However, the use of pesticides can be done below the economic threshold level so that the pest does not develop any resistance towards the chemicals.